Mentoring and Assistance of Women Farmers Groups (WFG) in South Tangerang City to Increase Yields and Sustainability through Value Chain - Imaroh, Tukhas Shilul; Nurhayati, Mafizatun; Hidayat, Imam; Nugroho, Rosalendro Edi; Belyarosa, Belyarosa; Nurafni, Sinta; Rahmansyah, Mohammad Zaky (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The 2024 community service program, funded by the Ministry of Research, Technology, and Higher Education, was carried out in the Women Farmers Group (WFG) Cempaka Batan Indah, South Tangerang, which manages a Sustainable Food House Area. WFG produces various healthy vegetables and fresh fish, with its main products being Butterfly Pea Flowers, Sacha Ichi, and Cumin. However, WFG faces supply chain challenges, including suboptimal production due to inefficient task division and low member awareness. Additionally, product distribution and packaging remain inadequate, leading to delivery obstacles. Profitability is also limited, as sales turnover does not meet expectations, and processing facilities are insufficient to achieve target production. To address these issues, the program provided training and coaching on organization, marketing, production quality, and productivity improvement. Members were also educated on the importance of the Supply Chain and Value Chain. Additionally, appropriate technology support was introduced with a dehydrator and an automatic vertical sealer to enhance production efficiency. As a result, members demonstrated increased understanding, enthusiasm, and capability in using the machines, leading to a threefold increase in production capacity. The process became more efficient, hygienic, and standardized, improving product quality and ensuring business sustainability.